Falsafat dan Tasawuf sebuah Misteri Peradaban (Dialog Pertemuan antara Pemikiran dan Perasaan, Problema Ibn Tufail dan Ibn 'Arabi) - T. Safir Iskandar Wijaya (Islam Futura, 2001)
In history, the development of Islamic thought includes of a variety of topics that were adopted later by both philosophers and Sufis. Indeed, the polemics frequently led to the murder of certain school leaders and its followers, such as in the case of Sufi leaders: Abu Mansur al Hallaj and Sharwardi al-maqtul. This is in contrast with Muslim philosophers, who still survived in spite of the fact that their thoughts were totally in opposite to theological tenets of society. Therefore, the question arise as to the relation between falsafah and tasawwuf. For this purpose, the idea of falsafah and tasawwuf of ‘Ibn Tufail and ‘Ibn ‘Arabi is worth studying. This study shows that both thinkers tried to combine these two subjects in achieving the truth; that is in spite of the fact that both falsafah and tasawwuf employed two different approaches in reaching the truth, the former through reason, while the later through define guidance.